(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The topicality of the topic: The agricultural sector is vital to the national economy. A key factor in maintaining the well-being of the population is the human resource to specific activities in the sector, in the context of the common European agricultural policy union. The research aims to assess the human factor as a tool for achieving sustainability in the agricultural sector of the economy. In terms of methods – in the study are used statistical methods, including arithmetic mean (arithmetic average) value, median, fashion. The development focuses on finding new income opportunities in the agricultural sector and tracking the digital skills of the population - with an emphasis on the Human Development Index - The Digital Economy and Society Index (DESI). The main results of the study of the achievements of human capital development are reduced to the identified need for new knowledge, respectively the growing need to acquire and maintain modern skills. This applies as a matter of priority to the managers of agricultural and livestock farms without completed education in the field of agriculture. This requires permanent qualification and retraining of employees in the agricultural sector. In conclusion, there is an opinion that the development of human potential requires training adequate to current technologies. The limited land as a resource for production requires the search for new opportunities for income in the agricultural sector. Regarding the research novelty on the developed issues - digital skills are perceived as a major factor in determining human capital, from this position the achievements in the individual member states of the European Union are followed. Study limitation - access to current public data. The development of a sustainable national agricultural sector is a guarantee of food security and independence, vibrant rural areas and employment of the local population.